Analisis pengaruh dana desa, alokasi dana desa, bagi hasil pajak dan retribusi, pendapatan asli desa dan luas wilayah terhadap belanja desa bidang pembangunan desa - Rahayu, Retno Puji; Pratiwi, Desy Nur; Kusuma, Indra Lila (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This study aims to analyze the impact of the Village Fund Allocation, Village Fund, Revenue Sharing of Taxes and Levies, Village Original Income, and Area Size on Village Expenditure in the field of Village Development. This research utilizes quantitative methods and utilizes secondary data gained from the Village Information System of Sukoharjo Regency and the Central Bureau of Statistics. The villages in the Sukoharjo Regency comprise the study's population. Purposeful sampling technique was employed, yielding a resulting sample of 149 villages. The results showed that the Village Fund, Village Fund Allocation, and Village Original Income had a substantial impact on village expenditure in the field of village development. At the same time, the Revenue Sharing of Taxes and Levies and the area does not have a substantial impact on village spending in the field of village development.